The Extent of Kindergarten Teachers’ Knowledge in Applying Artificial Intelligence Technology in the First Irbid District: Reality of Application and the Most Prominent Challenges from their Viewpoint - Saleh, KHitam Ali (Indian Journal of Information Sources and Services, 2025)
The current study aimed to identify the extent to which kindergarten teachers know how to apply artificial intelligence technology in the First Irbid District: the reality of application and the most prominent challenges from their viewpoint. To achieve this objective, a questionnaire was designed, and the sample consisted of (361) teachers. The results indicated that the arithmetic means for the items related to the level of knowledge in using artificial intelligence applications in teaching ranged between (3.14) and (3.21), with a moderate degree. The findings also showed that the arithmetic means for the items regarding the reality of employing artificial intelligence applications were moderate. Furthermore, the study revealed that the arithmetic means for the items related to the challenges of employing artificial intelligence applications were at a high level. The researcher recommended integrating artificial intelligence concepts and technologies into the kindergarten curriculum. Additionally, it emphasized the need for proper guidance and training to understand how to use and apply artificial intelligence applications in the teaching process. Teachers should also be provided with resources and continuous training to keep up with the latest technologies and best practices for smart learning.